PENDAMPINGAN PENGELOLAAN PERSEDIAAN BARANG KELUAR DAN MASUK BERBASIS MICROSOFT EXCEL PADA UMKM PECI BATIK DI JOGOKARIYAN - Ayu Nadilla Astuti; Zaenal Wafa (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy, but in practice, many MSMEs do not fully record their inventory. This problem occurred at the Jogokariyan Batik Peci MSME, where stock recordng was only done on outgoing goods, while incoming goods were not recorded. This activity aims to help the Jogokariyan Batik Peci MSME in improving the system of recording incoming and outgoing inventory to make it more organized and easier to understand. The methods used include observation, training and mentoring, and evaluation. Observations were conducted to determine the initial condition of inventory recording, followed by training and mentoring in preparing incoming and outgoing stock recording formats using Microsoft Excel. The evaluation stage was conducted to see the understanding of MSME owners in implementing independent stock recording. The results of the activity showed that this mentoring helped MSME owners in recording inventory more completely, thus making stock management more organized.